Improved antithrombotic activity and diminished bleeding side effect of a PEGylated αIIbβ3 antagonist, disintegrin. Issue 143 (July 2016) - Hsu, Chun-Chieh; Chuang, Woei-Jer; Chung, Ching-Hu; Chang, Chien-Hsin; Peng, Hui-Chin; Huang, Tur-Fu
Abstract: Introduction: The applicability of protein drugs is confined by protein degradation and rapid elimination. PEGylation of polypeptides improves protein stability by sterically obstructing the degradation by serum proteases and reduces renal clearance by the increased mass. Experimental approach: We compared the antithrombotic activities of intact rhodostomin (Rn) and PEGylated rhodostomin (PRn) both in vitro and in vivo systems. In addition, the functional half-life in inhibiting platelet aggregation and the tendency in causing bleeding side effect were investigated. Results: Rn and PRn both potently inhibited human and mouse platelet aggregation induced by collagen, thrombin or ADP in vitro with a similar IC50 around 60–100 nM. Rotational thromboelastometry assay indicated that PRn was more effective than Rn in preventing clot formation in human whole blood. In platelet-rich plasma from mice injected with Rn or PRn, the inhibitory effects on collagen-induced platelet aggregation were also comparable, but Rn caused higher bleeding tendency. In ferric chloride-induced arterial thrombosis, Rn and PRn significantly prolonged occlusion time at high dosage (0.2 μg/g). However, PRn obviously prolonged the occlusion time even given at a lower dosage (0.06 μg/g). The functional half-life assay revealed that PEGylation prolonged the in vivo half-life of Rn. Conclusions: PRn exhibits higher antithrombotic potency and longer half-life in vivo as compared with native Rn on a molar basis. In addition, PRn exhibits a better safety profile at an efficacious antithrombotic dose in vivo . Therefore, PEGylation may be one of the ideal options in modifying disintegrin derivatives as the safe therapeutic agents for integrin-related diseases. Highlights: PEGylated Rn (PRn) is a better αIIbβ3 antagonist than native Rn therapeutically. PRn has a higher antithrombotic potency and longer half-life in vivo . PRn exhibits a better safety profile at the antithrombotic dose in vivo . PEGylation is an ideal modification of disintegrin in integrin-related therapies.